Editorial: XVII IOSTE Symposium - Science and Technology Education for a Peaceful and Equitable World - Carvalho, Graça Simões de (2017)
The IOSTE Symposium occurs every two years in a different country. The latest event was organized by the Research Centre on Child Studies, of the University of Minho (CIEC-UM), in Braga (Northern region of Portugal): “IOSTE Symposium - Science and Technology Education for a Peaceful and Equitable World”, 11-16 July 2016 (http://www.eventos.ciec-uminho.org/ioste2016/). The authors of 303 works presented at the XVII IOSTE Symposium were invited to submit a full paper of their communications. Of the 79 received papers, 66 were accepted for the proceedings of this special issue of the journal Conexão Ciência.